Big data meets survey science : a collection of innovative methods - Hill, Craig A., 1956-; Biemer, Paul P.; Buskirk, Trent D., 1971-; Japec, Lilli, 1966-; Kirchner, Antje, 1982-; Kolenikov, Stanislav; Lyberg, Lars (Wiley series in survey methodology., 2021)
"Written and painstakingly edited by leading experts in their respective fields, this volume offers a state-of-the-art overview of Big Data issues, concerns, and responses in survey methodology. Like several other books in the Wiley Series in Survey Methodology, this work has been prepared in conjunction with an international conference on the topic by the Survey Research Methods Section of the American Statistical Association. The conference and book constitute part of an ongoing effort by a group of international researchers to promote quality in Big Data and to raise the level of methodological expertise in various applied fields. The basic content, in light of emerging techniques and technologies, includes in-depth coverage of topics such as combining Big Data with traditional data sources; multiplicity; data sparseness; data streams; using Big Data for reducing, controlling, and evaluating total survey error; handling confidentiality and privacy; and ethical concerns and the concept of harm; among a host of others. The editors and contributors are eminent, varied, and reflective of the international marketplace. Copious tables, figures, and references, as well as an extensive glossary, supplement the high quality discussion throughout the text"--